Analisis Penerapan Dana Bantuan Operasional Sekolah (BOS) dan Dana Penunjang Pendidikan (DPP) dalam Upaya Meningkatkan Kinerja Keuangan Sekolah - Siddiq, Alwi Rofiudin; Nurmilah, Risma; Himawan, Irfan Sophan (Ikatan Da'i Indonesia, 2024)
This study aims to analyze the application of the School Operational Assistance Fund (BOS) and the Education Support Fund (DPP) in an effort to improve school financial performance. This research focuses on the period 2019 to 2024 with the place used as the object of research is SD Negeri Pasirmunding Kabupaten Sukabumi, for the research method used in this research is descriptive qualitative research method with a case study approach by means of data obtained through interviews, observations, and document analysis related to the management of BOS and DPP funds at the school. The results showed that the management of BOS and DPP funds at the school had been carried out in accordance with the technical guidelines stipulated by the Permendikbud although there were several indicators that had not been met, especially in the summarization stage, and the reporting stage, namely the stage of making balance sheets, balances, journals, adjusting journals, preparing working papers, closing journals, making balance sheets after closing and making public journal paragraphs. As for the reporting stage that has not been achieved, namely the preparation of a surplus or deficit report, cash flow statement, balance sheet and financial statement notes, even though all of this is useful in knowing the fraud that occurs and is useful in decision making. Determining the right allocation of funds and efficient use of funds contributes greatly to improving school financial performance. In addition, transparent and accountable fund management also increases public and stakeholder trust in school financial management. However, the study also identified some challenges, such as limited human resources in fund management and the need to improve the capacity of financial managers in schools. The study concludes that the effective implementation of BOS and DPP funds is crucial to improving school financial performance but further efforts are needed to overcome the challenges to optimize fund management.